Use of surgery and carboplatin in feline malignant mammary gland neoplasms with advanced clinical staging - Campos, Cecilia Bonolo de [UNESP]; Nunes, Fernanda Camargo; Lavalle, Gleidice Eunice; Cassali, Geovanni Dantas [UNESP] (Int Inst Anticancer Research, 2014)
Background/Aim: Feline mammary carcinomas (FMCs) are characterized by poor prognosis and little progress has been made in extending patient survival. The aim of the study was to compare overall survival periods of FMCs submitted to different treatment protocols, including surgery and adjuvant chemotherapy. Materials and Methods: Analysis of conventional surgical excision alone or in association with adjuvant chemotherapy with carboplatin in sixteen cats diagnosed with stage III and grade II or III FMCs was performed. Results: Patients treated with surgery and chemotherapy presented a longer overall survival (OS) than those treated only with surgery, however, no statistical difference was observed when comparing both treatments (p=0.883). Conclusion: Therapeutic benefit of carboplatin remains invalidated for FMCs and further investigation regarding adjuvant therapies are warranted. Surgery remains as the gold treatment in FMCs.
Keywords: Feline; mammary gland; neoplasm; chemotherapy; carboplatin